Prospective study of fetomaternal outcome in eclampsia in a tertiary care hospital - C., Raji; M., Poovathi; D., Nithya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Objective of the study was to evaluate fetomaternal outcome in patients with eclampsia. Methods: This prospective study was conducted in Government Thanjavur Medical College Hospital, Tamilnadu, India over a period of 15 months from January 2015 to March 2016 in all eclampsia cases. Total 146 eclampsia cases were admitted of which 113 were antepartum eclampsia, 4 were intrapartum eclampsia and 29 cases were postpartum eclampsia. In all cases of antepartum eclampsia pregnancy was terminated irrespective of gestational age. Results: This study showed that incidence of eclampsia in our hospital is 0.83%. It is more common in the age group of 20 to 25 years (78.8%) and primigravidae (69.2%). Maximum number of cases had seizures before the onset of labour (77.39%). 53.85% eclamptic cases presented with seizures at ≥37 completed weeks. Commonest mode of delivery was caesarean section (62.33%). Out of 146 patients, 9 (6.16%) cases died, 35 (23.97%) had complications. 75.64% cases delivered live babies but 26.36% had early neonatal death. Conclusions: Eclampsia is still one of the important and common obstetric emergencies, which has a significant role in maternal and perinatal outcome. Regular Antenatal Care (ANC), proper health education, improvements of socio-economic conditions and spreading of awareness in the community has major roles in prevention of eclampsia. Timely and appropriate intervention including primary management, early referral and judicious termination of pregnancy help in reducing morbidity and mortality of both mother and fetus.